(untitled) (África, 2009)
Using the systemic, structural and contrastive linguistic theories as base of analysis, the paper identifies and explicates eighteen English-translated Yoruba proverbs associated with women and brings out their inadequacies with regard to gender prejudice against the female race. Out of the eighteen, fourteen are found to be gender-biased while only four of them are gender-neutral and can apply to both sexes. From the foregoing, it suggests the second versions of these proverbs that cater for the gender not represented in the first set. Thus, the paper is able to prove that the same set of proverbs can be used as reprimand for both the female and male sexes and not only one of them as they were originally.